Broken ebook - Winslow, Don (2020)
Includes "Crime 101," "Broken," and "The Last Ride" – all soon to be major motion pictures! "One of America's greatest storytellers." – Stephen King " Winslow, whose work includes a dozen of the finest crime novels written in the last 20 years, displays all of his strengths, including propulsive narration, compelling characters and a tight, staccato writing style, in 'Broken,' a collection of six remarkable novellas." – Bruce De Silva, Associated Press No matter how you come into this world, you come out broken . . . In six intense short novels connected by the themes of crime, corruption, vengeance, justice, loss, betrayal, guilt and redemption, Broken is #1 international bestseller Don Winslow at his nerve-shattering, pulse-pounding, heartbreaking best. In Broken, he creates a world of high-level thieves and low-life crooks, obsessed cops struggling with life on and off the job, private detectives, dope dealers, bounty hunters and fugitives, the lost souls driving without headlights through the dark night on the American criminal highway. With his trademark blend of insight, humanity, humor, action, and the highest level of literary craftsmanship, Winslow delivers a collection of tales that will become classics of crime fiction. "With the passing of Elmore Leonard a few years back, it's now safe to proclaim Winslow America's greatest living crime writer. His consistency is matched only by his creativity, his talent exceeded by his ability to surpass himself time and time again." – Jon Land, Providence Journal